The efficacy of platelet rich plasma in the treatment of erectile dysfunction: a systematic review and meta-analysis of randomized controlled trials - Qiancheng Mao; Yingying Yang; Yang Liu; Hongquan Liu; Gonglin Tang; Xiaofeng Wang; Yuanshan Cui; Jitao Wu (The Aging Male)
Background Erectile dysfunction (ED) is a common issue among males, and the use of platelet-rich plasma (PRP) therapy for treating ED has gained increasing attention, but there is still no conclusive evidence regarding its efficacy.Aim To evaluate the efficacy of PRP therapy for ED.Methods We systematically searched PubMed, Embase, Cochrane Library, and Web of Science databases up to November 2023 to identify randomized controlled trials (RCTs) on PRP therapy for ED. We used Review Manager version 5.4 for data analysis and management.Result After applying inclusion and exclusion criteria for screening, a total of 4 studies involving 413 patients were finally included in our meta-analysis. According to our analysis, the PRP group showed significant advantages over the placebo group in terms of MCID at the first month (p = 0.03) and sixth months (p = 0.008), while there was no significant difference between the two groups at the third month (p = 0.19). Additionally, in terms of IIEF, PRP showed significantly better efficacy than placebo at the first, third, and sixth months (p < 0.00001).Conclusions PRP shows more effectiveness in treating ED compared to placebo, offering hope as a potential alternative treatment for ED.